2011
DOI: 10.1021/np100797y
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids from Eight Tropical Plant Species That Inhibit the Multidrug Resistance Transporter ABCG2

Abstract: Overexpression of ABCG2, a membrane-bound multidrug transporter, can make tumor cells resistant to treatment with conventional chemotherapeutic agents. A high-throughput screening effort with the NCI repository of natural product extracts revealed that eight tropical plant extracts significantly inhibited the function of ABCG2. This activity was tracked throughout the extract fractionation process to a series of ABCG2 inhibitory flavonoids (1–13). Their structures were identified by a combination of NMR, mass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…Two milbemycin compounds (Gao et al, 2011), two novel acrylonitrile derivatives (Yamazaki et al, 2011), and a number of benzo(a)quinolizin-4-ones (Kanintronkul et al, 2011) showed chemosensitizing properties attributable to modulation of P-gp, whereas X-shaped poly-(ethylene oxide)-poly(propylene oxide) block copolymers (poloxamines) inhibited P-gp and BCRP in hepatic carcinoma cell lines (Cuestas et al, 2011). A number of flavonoid compounds from various plant species were shown to inhibit BCRP function (Versiani et al, 2011) and to inhibit vinblastine-stimulated P-gp activity but to promote daunorubicinstimulated P-gp activity in leukemic T cells (Tran et al, 2011). Limonin and other citrus compounds enhanced doxorubicin cytotoxicity in MDR CEM/ADR5000 leukemia cells (El-Readi et al, 2010).…”
Section: Downloaded Frommentioning
confidence: 99%
“…Two milbemycin compounds (Gao et al, 2011), two novel acrylonitrile derivatives (Yamazaki et al, 2011), and a number of benzo(a)quinolizin-4-ones (Kanintronkul et al, 2011) showed chemosensitizing properties attributable to modulation of P-gp, whereas X-shaped poly-(ethylene oxide)-poly(propylene oxide) block copolymers (poloxamines) inhibited P-gp and BCRP in hepatic carcinoma cell lines (Cuestas et al, 2011). A number of flavonoid compounds from various plant species were shown to inhibit BCRP function (Versiani et al, 2011) and to inhibit vinblastine-stimulated P-gp activity but to promote daunorubicinstimulated P-gp activity in leukemic T cells (Tran et al, 2011). Limonin and other citrus compounds enhanced doxorubicin cytotoxicity in MDR CEM/ADR5000 leukemia cells (El-Readi et al, 2010).…”
Section: Downloaded Frommentioning
confidence: 99%
“…This compound gave NMR parameter which is suitable with 4′-Omethyl-8-isoprenyleriodictyol from M. conifera [5].…”
Section: Resultsmentioning
confidence: 94%
“…Compound 1 depicted a negative Cotton effect originating from a π π* transition at 290 nm, and this was adequately indicative of a 2S configuration. 12,13) The stereochemistry of C-9 still remains to be determined since the inadequate rotating frame nuclear Overhauser enhancement spectroscopy (ROESY) correlations and the failure to obtain suitable crystal for single X-ray diffraction analysis. Based on these results, the structure of 1 (neougonin A) was assigned as 5,7,3′,4′-tetrahydroxy-6-(2,6-dimethyl-6-vinyl-2-hexenyl)-flavanone.…”
Section: Resultsmentioning
confidence: 99%